Design of Multiband Antenna using Fringing Effects of Metamaterials - Dang, Nhu Dinh; Hoang, Phuong Chi; Dao, Ngoc Chien (Old Journal, 2017)
A design of multiband microstrip antenna based on fringing effects of metamaterials is proposed in this paper. The proposed antenna is printed on FR4 substrate with a dielectric constant of 4.4 and a thickness of 1.6 mm. The antenna is constructed by two spiral branches and each branch are composed by many strip segments. The resonant frequency bands of proposed antenna can be calculated and controlled by using fringing effects of metamaterials that depends on the value of the gap between the segments of each spiral branch. Besides, mutual induction is used to suppress the harmonics between the designed frequencies in order to create a multiband resonance. The proposed antenna is optimized to operate at the frequency bands of 4G (1.8 GHz), WLAN (2.4 GHz) and WiMAX (3.5 GHz). The measured S11 of fabricated antenna shows that the antenna can resonate at three -10 dB bandwidths of (1.70-1.96) GHz, (2.34-2.57) GHz and (3.43-3.78) GHz.